2022
DOI: 10.17221/147/2021-pps
|View full text |Cite
|
Sign up to set email alerts
|

Phages of phytopathogenic bacteria: High potential, but challenging application

Abstract: Phytopathogenic bacteria are one of the most significant causes of crop yield losses. Until now, the direct treatment of bacterioses was limited to the application of antibacterial compounds or resistance inducers. This is about to change due to the revolutionary discovery of phages. Indeed, bacteriophages look very promising as therapy agents: cheap, self-amplifying, self-eliminating, and safe for the host organism. However, phage therapy of plant diseases remains a “direction with high potential”, which, so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In recent years, phages have been isolated against bacteria infecting the majority of crops. Several studies showed that phage therapy using lytic bacteriophages was plausible for controlling plant pathogenic bacteria associated with several systems as they are cheap, self-amplifying, self-eliminating, and safe for the host organism ( Korniienko et al, 2022 ). Due to ineffective chemical control methods, increasing antimicrobial resistance, and increasing environmental concerns, bacteriophages offer alternative management strategies for controlling plant diseases caused by bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, phages have been isolated against bacteria infecting the majority of crops. Several studies showed that phage therapy using lytic bacteriophages was plausible for controlling plant pathogenic bacteria associated with several systems as they are cheap, self-amplifying, self-eliminating, and safe for the host organism ( Korniienko et al, 2022 ). Due to ineffective chemical control methods, increasing antimicrobial resistance, and increasing environmental concerns, bacteriophages offer alternative management strategies for controlling plant diseases caused by bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…oryzae XooCG01 at 28°C. The phage NR08-treated (orange color line) bacterial count showed bacteriostasis up to 24 h as compared to bacterial control (blue color line); thereafter, the reduction in the count was 99.95% as compared to untreated bacterial control at 48 h. controlling plant pathogenic bacteria associated with several systems as they are cheap, self-amplifying, self-eliminating, and safe for the host organism (Korniienko et al, 2022). Due to ineffective chemical control methods, increasing resistance, and increasing environmental concerns, bacteriophages offer alternative management strategies for controlling plant diseases caused by bacterial pathogens.…”
mentioning
confidence: 99%
“…The most relevant phytopathogen bacteria responsible for damaging crops and affecting food production around the world are Pseudomonas spp., Xanthomonas spp., Pectobacterium spp., Ralstonia spp., Burkholderia spp., Dickeya spp., Clavibacter ichiganensis , and Agrobacterium tumefaciens [ 177 ]. To combat these phytopathogens, the bulk of isolated phages are tailed ones (mainly from the Podoviridae or Myoviridae families), although the use of filamentous phages has also shown considerable potential [ 32 ].…”
Section: Phage Delivery Strategies For Plant Healthmentioning
confidence: 99%
“…For plant crops, bacteriophage-based biocontrol has been used on several important bacterial plant pathogens, with very promising results [ 30 ]. In this way, over the years, many bacteriophages against many plant-pathogenic bacteria have been isolated from environmental sources, and diverse studies have shown that their use allows for the efficient management of disease development in both controlled (greenhouse) and open (field) conditions [ 31 , 32 ]. Nowadays, several phage-based biocontrol products have reached the market [ 30 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…are among the most popular hosts for novel phage isolation ( Zrelovs et al, 2021b ). Moreover, novel phages infecting P. syringae are being constantly isolated and described, largely in search for appropriate P. syringae biocontrol agents among them ( Korniienko et al, 2021 ). For example, a highly effective commercially available phage φ6 was found to be efficient against P. syringae pv.…”
Section: Introductionmentioning
confidence: 99%